Risks in Children’s Digital Visibility and Vulnerability: Sharenting in France, Italy, Spain, and the United Kingdom - Suárez-Álvarez, Rebeca; Pastor-Rodríguez, Ana (European Public & Social Innovation Review, 2025)
Introduction: Sharenting has become a common practice in which parents publicly share aspects of their children's lives on social media platforms. This study explores how parent influencers manage their children's visibility, vulnerability, and privacy, as well as the underlying purposes of sharenting. Methodology: Through a comparative approach, the practices of 12 parent influencers—mothers and fathers—from France, Italy, Spain, and the United Kingdom are examined. A total of 1,789 posts on Instagram and TikTok are analysed using content analysis. Results: Cultural differences are identified in the representation of parental roles: mothers take on a leading role, particularly in Italy, while French male influencers frequently depict involved fatherhood. A concerning trend is observed regarding the lack of safeguards to protect children's identities, increasing the risks associated with their digital exposure. Sharenting is not primarily commercial – the UK is the country where children are most used for promotional purposes – nor is it a space for parental support. Discussions: This study critically examines how mediated parenthood and child representation are negotiated in contemporary digital communication. Conclusions: Influencers, as parents, construct self-representations of themselves as caring and competent caregivers embedded within the logics of digital entertainment.